2007
DOI: 10.1111/j.1525-1470.2007.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Planus in African Children: A Study of 13 Patients

Abstract: Lichen planus is an uncommonly encountered dermatosis in children, reported worldwide, however in sub-Saharan Africa there is paucity of data on Lichen planus among children. The aim of this study was to document the clinical types of Lichen planus observed in children in South East Nigeria from 1998 to 2001; and to highlight any differences and similarities with adult disease. In all, 13 patients (eight boys and five girls) aged between 3 and 15 years were diagnosed with Lichen planus. The limbs were the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…Nail involvement may irreversibly deform or destroy the nails. Dorsal pterygium is one of the characteristic findings and may be present in the classic form [53, 57]. Twenty-nail dystrophy is characterized by nail coarseness affecting all fingernails and toenails because of excessive longitudinal ridging (trachyonychia).…”
Section: Resultsmentioning
confidence: 99%
“…Nail involvement may irreversibly deform or destroy the nails. Dorsal pterygium is one of the characteristic findings and may be present in the classic form [53, 57]. Twenty-nail dystrophy is characterized by nail coarseness affecting all fingernails and toenails because of excessive longitudinal ridging (trachyonychia).…”
Section: Resultsmentioning
confidence: 99%
“…While LP is generally considered an adult disease, 5 to 10% of cases do occur in children (Kumar et al, 1993, Luis-Montoya et al, 2005), the majority of which are reported in India (Handa and Sahoo, 2002, Kanwar and De, 2010, Kumar et al, 1993, Pandhi et al, 2014, Sharma and Maheshwari, 1999). In the childhood population, onset is more common in school-aged children, with mean reported age ranging from 7 to 11.8 years old, though infantile cases have rarely been reported (Balasubramaniam et al, 2008, Handa and Sahoo, 2002, Kanwar and De, 2010, Luis-Montoya et al, 2005, Nanda et al, 2001, Nnoruka, 2007, Pandhi et al, 2014, Walton et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…It occurs uncommonly in children. It was observed that patients with actinic LP attended the clinic earlier (3.9 months) due to acute onset of the lesions and cosmetic reasons as compared to other variants of LP [11][12][13]. Histopathology of the lesions revealed band like mononuclear infiltrate (Fig.…”
Section: Discussionmentioning
confidence: 98%